The genus Stilobezzia Kieffer (Diptera: Ceratopogonidae) in Argentina: a new species, new records, and first description of the female of S. chaconi Kieffer - Cazorla, Carla; Rossi, Juan Francisco; Marino, Pablo I. (Zootaxa, 2026)
A new species of predaceous midge, Stilobezzia (Acanthohelea) gustavoi sp. nov., is described and illustrated. The previously unknown female of Stilobezzia (Stilobezzia) chaconi Macfie is described and illustrated for the first time. The male of S. chaconi is redescribed, and the species is recorded from Argentina for the first time. Stilobezzia (S.) albicoxa Lane & Forattini and Stilobezzia (Eukraiohelea) proxima Cazorla & Felippe Bauer are newly recorded from Argentina, Stilobezzia (S.) punctulata Lane is newly recorded from Misiones province, and S. (S.) rabelloi Lane newly recorded from Misiones and Entre Ríos provinces. An annotated checklist of Stilobezzia species from Argentina, comprising a total of 43 species, is provided.